Подання функцій щільності ймовірності розподілів ДКП коефіцієнтів JPEG зображень кривими пірсона - Цариценко, С. Д.; Федоров, О. В. (ХНУРЕ, 2020)
The paper employs technique of Person’s curves to approximate and discover properties of the DCT coefficient densities of JPEG images. In particular, the conducted research has shown that beta distribution of the 2-nd type provides good agreement with the empirical data. Despite the fact that our research is focused on JPEG images, research output is going to be applicable to a much broader selection of contemporary image formats as many of them are DCT based.